Shear bond strength after various recycling processes of rebonded damon brackets: a comparative in vitro study. - Mutar, Saja S; Mohammed-Salih , Harraa S; Al-Obaidi, Jameel R; Supian, Faridah L; Azmi , Mohd SM (Journal of Baghdad College of Dentistry, 2025)
Background: This study aims to investigate the effect of various recycling techniques on metal self-ligating Damon brackets’ shear bond strength. Materials and methods: Fifty-four Damon Q self-ligating brackets in total were split into two different groups: the first group, which included the control group, had 18 new brackets, and the second group, which included 36 new brackets that were bonded to typodont and then debonded using a tweezer. Eighteen debonded brackets were split into two experimental groups for recycling (sandblasting and tungsten carbide bur). The fifty-four removed upper first premolar teeth were then fitted with all of the brackets using a uniform bonding technique. Every specimen’s shear bond strength was assessed using a universal testing machine until the bond breakup. The data were statistically analyzed using the ANOVA F-test in SPSS version 26. P ≤ 0.05 was considered significant for all statistical tests‏. Result: Using the ANOVA F-test, it was found that there were significant differences in the mean value of the shear bond strength for each group. Moreover, the mean value of shear bond strength for the new bracket group had the highest value (5.99± 0.40 MPa), followed by the sandblasting group (5.94 ± 0.11 MPa), and the tungsten carbide bur group had the lowest value (4.27± 0.75 MPa). Conclusion: For repositioning of rebounded Damon brackets, shear bond strength that is clinically acceptable would be produced by the sandblasting procedure, while the tungsten carbide bur method would result in lower shear bonding strength and bracket base mesh loss.